Death Caused by Honey Bee Stings: Case Report - Nezih Anolay; Murat Nihat Arslan; Bahadir Kumral; Yalcin Buyuk (Medicine Science, 2014)
A bee sting is always potentially serious. The severity and duration of a reaction can vary from one person to another. In addition, one's own reaction to a bee sting may differ between occurrences. Most persons experience a local non-serious allergic reaction to bee venom. However, depending on the location and number of bee stings received, as well as the ever-present possibility of a severe allergic reaction to bee venom, a serious reaction can be precipitated that can be life-threatening. A 49 years old man having a history of allergic reaction to bee sting was found dead near to 9 nests. There were many dead honey bees on him. External examination of the body showed more than 50 stings all over the body. Upon medico-legal autopsy, pulmonary edema and swelling in laryngeal area were the internal findings. History of allergy, autopsy findings and findings obtained from crime scene investigation were evaluated together and the cause of death was concluded to be anaphylactic shock resulted from bee stings. [Med-Science 2014; 3(2.000): 1305-14]